Crash Safety of High-Voltage Powertrain Based Electric Vehicles Electric Shock Risk Prevention - Gong, Chao.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book systematically introduces fast winding-based discharge strategies used for permanent magnet synchronous machine-based drives in electric vehicles (EVs) after a crash. The contents are from the author's final thesis securing his Ph.D. degree. The book contains seven chapters. Chapter 1 introduces the motivation of the research. Chapter 2 reviews five types of injury hazards that the occupants might suffer during crashes, addressing the high-voltage problem. In Chapters 3, 4, and 5, different winding-based discharge techniques are developed. Chapter 6 discusses the general principles for selecting an effective and efficient discharge technique for a particular EV. The conclusion is drawn in Chapter 7. Some author's achievements are listed at the end of the book. This book introduces professional knowledge about the subject of electrical engineering. It can be used as a reference book for technicians and scholars in this area.
Introduction -- Review of EV Safety in Crash Conditions -- New Winding-based Discharge Strategy for EV Powertrains with Extreme Parameters -- Hybrid DC-Bus Capacitor Discharge Strategy for EV Powertrains with Highly Extreme Parameters -- Fault-Tolerant Winding-based DC-Bus Capacitor Discharge Strategy -- Winding-based Discharge Technique Selection Rules based on Parametric Analysis -- Conclusions and Future Work.
Keywords: Vehicles; Electric power production; Automotive engineering; Fire prevention; Buildings$1 (BProtection.s; Vehicle Engineering; Electrical Power Engineering; Automotive Engineering; Fire Science, Hazard Control, Building Safety; Electric vehicles -- Power supply; Electric vehicles -- Crashworthiness